Effect of buoyancy force on buoyancy waterwheel efficiency using numerical flow simulation - Fadlurrahman Zaki; Dan Mugisidi (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
In this work, the performance of a buoyant waterwheel to produce hydrokinetic power is investigated through analytical theory and computational fluid dynamics simulation. The impact of the buoyancy wheel is investigated by establishing the performance parameters through the use of a moving mesh approach and a realizable k-ε turbulence model. Transient simulation is required to comprehend the flow of physical processes. Using moving mesh as a transient methodology of the buoyancy waterwheel, numerical flow simulations and theoretical analytical methods are used in this study to assess the effect of buoyant force generated on the performance of the buoyancy wheel. The buoyancy waterwheel that will be put to the test has eight straight blades and a diameter of one meter.  The pinwheel force and torque created in the numerical flow simulation (CFD) are 414.96 N and 207.48 Nm, respectively, whereas in the theoretical calculation they are 449.06 N and 224.53 Nm, according to the research findings. It is possible to compute the buoyancy wheel's power output and efficiency mathematically, yielding values of 1619.35 W and 68.07%. The buoyancy wheel's power output and efficiency, as determined by numerical flow simulation, are 1495.95 W and 62.88%, respectively. Based on theoretical and CFD study results, the buoyancy wheel generates a standard deviation of 7.62%. Thus, for the buoyancy wheel, a temporary method that makes advantage of the moving mesh characteristic is advised. This method can also be applied as a future alternative energy source for the Piko hydro turbine